發展中國家數位落差消弭之法－電子資料庫的建置與使用 Developing Nations, the Digital Divide and Research Databases - Sam Brooks; Paul Donovan; Clint Rumble (Jiàoyù zīliào yǔ túshūguǎn xué, 2006)
「數位落差影響著許多發展中國家」，此言意味著經費不足、電腦與網路技能的缺乏與英語能力的欠缺，以致使發展中國家數位資訊資源之擴展與使用受到阻礙。具有遠見之個人或組織可投入協助滿足發展中國家資訊需求之行列，匯集性全文資料庫可作為一種消弭數位落差的絕佳工具，參與此任務之組織必須對使用者展現資源的價值並提供必要的訓練，以確保計畫之成功。 The digital divide affects many nations of the developing world. The term encompasses inadequate funding, a lack of necessary computer and Internet skills, a lack of English-language proficiency that hinder expansion and use of digital information resources. Visionary individuals and organizations can assist these countries with their information needs. Aggregated full-text databases serve as a prominent tool in closing the digital divide because they provide important research resources. Participating organizations must demonstrate the value of these resources to users and supply essential training to ensure success with electronic resource initiatives.